Exploring VR and Neuroscience Methodologies in Interior Design: A Systematic Review - Yasemin Albayrak-Kutlay; Murat Bengisu (Human Behavior and Emerging Technologies)
The intersection of neuroscience and interior design offers innovative methodologies for quantifying human experiences in interiors. This systematic review explores the use of immersive virtual reality (IVR) technologies and biometrics in neuroscience-informed interior design, aimed at evaluating current practices, identifying challenges, and suggesting future directions. This study has three objectives: (1) to examine the current applications of integrated VR/neuroscience methodologies in neuroscience-informed interior design; (2) to investigate the utilization of IVR technologies, devices, and sensors measuring biometrics employed in neuroscience-informed interior design to quantify human experience; and (3) to explore potential future directions in interior design that integrate insights from neuroscientific research findings and methodologies. Using the PRISMA methodology, we searched databases, including Taylor and Francis Online, ProQuest, PubMed, PsycINFO, Web of Science, Scopus, and ScienceDirect, in October 2023, retrieving 164 eligible studies, with 29 reviewed in detail. The risk of bias was assessed by paying attention to randomization, intervention deviations, outcome measurement, and the selection of reported results. The findings highlight the critical role of IVR and biometric analysis in enhancing research validity. However, variability in data reliability and differences between self-assessed and neurophysiological outcomes, particularly in EEG studies, have been noted. Despite these limitations, the reviewed studies present reliable findings, underscoring the potential for interdisciplinary collaboration to address technical challenges. Practical implications include advancing evidence-based interior design and developing tools to capture and interpret human experiences better. This study provides designers with a detailed analysis of IVR and neuroscience methodologies, highlighting tools, outcome measures, and their advantages and limitations. Future research should prioritize deeper insights into human–environment interactions through artificial intelligence (AI), machine learning (ML), and biometric sensors integrated with IVR technologies. These advancements will equip designers with interdisciplinary methods and emerging technologies to create innovative interiors that enhance the quality of life.